2022
DOI: 10.3390/biom12020275
|View full text |Cite
|
Sign up to set email alerts
|

Role of Urinary Kidney Stress Biomarkers for Early Recognition of Subclinical Acute Kidney Injury in Critically Ill COVID-19 Patients

Abstract: A high proportion of critically ill patients with COVID-19 develop acute kidney injury (AKI) and die. The early recognition of subclinical AKI could contribute to AKI prevention. Therefore, this study was aimed at exploring the role of the urinary biomarkers NGAL and [TIMP-2] × [IGFBP7] for the early detection of AKI in this population. This prospective, longitudinal cohort study included critically ill COVID-19 patients without AKI at study entry. Urine samples were collected on admission to critical care are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…According to new research, elevated NGAL in urine can detect AKI as early as 2 h ( Karademir et al, 2016 ). Haase et al discovered that high NGAL levels were related with poor results even in the lack of diagnostic SCr elevations in a pooled data analysis of 10 studies of patients hospitalized to ICU ( Casas-Aparicio et al, 2022 ). Urine NGAL was shown to detect NSAID-mediated renal tubular injury in the initial phase of renal injury in a cohort study of children with congenital heart disease who underwent cardiopulmonary bypass (CPB), and urine NGAL had good diagnostic accuracy in identifying children receiving NSAIDs, with an AUC of 0.95–0.96 at 24–48 h after administration of NSAIDs.…”
Section: Subclinical Aki Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…According to new research, elevated NGAL in urine can detect AKI as early as 2 h ( Karademir et al, 2016 ). Haase et al discovered that high NGAL levels were related with poor results even in the lack of diagnostic SCr elevations in a pooled data analysis of 10 studies of patients hospitalized to ICU ( Casas-Aparicio et al, 2022 ). Urine NGAL was shown to detect NSAID-mediated renal tubular injury in the initial phase of renal injury in a cohort study of children with congenital heart disease who underwent cardiopulmonary bypass (CPB), and urine NGAL had good diagnostic accuracy in identifying children receiving NSAIDs, with an AUC of 0.95–0.96 at 24–48 h after administration of NSAIDs.…”
Section: Subclinical Aki Biomarkersmentioning
confidence: 99%
“…NGAL was also discovered to be an independent risk factor for COVID-19 patients ( He et al, 2021 ). In another cohort study, those with NGAL ≥45 ng/ml had a substantially shorter time to AKI than those with <45 ng/ml, but NGAL was not a risk factor for AKI during admission, and NGAL performed considerably better on day 7 than throughout hospitalization, implying that NGAL has a limited time window for predicting AKI and that higher NGAL thresholds appear to help predict the progression of AKI rather than the onset of AKI ( Casas-Aparicio et al, 2022 ). Because NGAL threshold value is still controversial, including NGAL in clinical prediction models to improve disease identification requires additional research.…”
Section: Subclinical Aki Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 85 ] demonstrated that the NGAL level was an independent predictor in predicting AKI. Recently, a series of studies have shown that NGAL displayed acceptable performance for predicting AKI, the need for RRT, and death [ 14 , 46 , 86 , 87 ]. In addition, one clinical trial was established to study the role of NGAL and CysC in the prediction of AKI in COVID-19 infection ( NCT04603664 ) .…”
Section: Kidney Injury Biomarkersmentioning
confidence: 99%
“…Gustavo et al. [ 86 ] demonstrated that elevated values of urinary [TIMP-2] • [IGFBP7] were risk factors for AKI. A clinical trial has been established to study whether TIMP-2 and IGFBP7 could identify patients with COVID-19 at risk of developing AKI early (NCT04393428), and the findings of this investigation will be made public in the future.…”
Section: Kidney Injury Biomarkersmentioning
confidence: 99%